Implementasi Metode Waterfall Pada Sistem Informasi Pendaftaran Sekolah Seni Tari Balet Berbasis Website (Studi Kasus: On Point Balet School) - Dicky Hariyanto; Muhammad Qomaruddin; Trivera Yolanda Sirait (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
In a place to learn to dance ballet from the ground up, ballet which is a classical dance originating from the European continent, more precisely from Italy but more developed in France and one of the fields of dance that is loved and followed by various groups, ranging from children until adulthood. On Point Ballet School is a ballet dance school that focuses on teaching ballet dance from the ground up. At this time there are many ballet dance courses whose service system still uses a manual system, especially in the registration section. The registration system used by On Point Ballet School is still manual. The method used in this system is the waterfall model, which is a classical model that is systematic, sequentially in building software. The name of this model is actually “Linear Sequential Model”. This model is often referred to as the "classic life cycle" or the waterfall method so that it can provide an alternative solution on the ballet art school registration system website to facilitate registration in obtaining up-to-date information about ballet art schools at the On Point Ballet School offered. Keywords: Registration System, Software, Waterfall